Direct analysis of phthalate esters in vegetable oils by means of comprehensive two-dimensional gas chromatography combined with triple quadrupole mass spectrometry. (1st December 2022) - Arena, Alessia; Zoccali, Mariosimone; Mondello, Luigi; Tranchida, Peter Q.
Highlights: A simple and "direct" method for phthalate analysis in vegetable oils is proposed. Sample preparation involved only dilution with a suitable solvent. Twenty-seven vegetable oils were analyzed by using GC × GC with triple quadrupole MS. Nine vegetable oils were found to be contaminated by DPP, DEHP, DiNP, and DiDP. Abstract: Phthalic acid esters (PAEs), known as phthalates, have a variety of industrial applications, mainly related to their ability to increase plastic softness, flexibility, and durability. With regard to toxicological aspects, several studies suggest that phthalates would act as endocrine-disrupting chemicals, and they have been correlated to several forms of cancer. Since the analysis of PAEs in food is challenging, the aim of this study was the development of a simple and direct method, with no sample preparation (only dilution with solvent), for the analysis of targeted phthalates in vegetable oils, by using cryogenic-modulation comprehensive two-dimensional gas chromatography combined with triple quadrupole mass spectrometry. The method was characterized by good repeatability values, limit of quantification values ranging between 0.06 and 2.10 mg/kg, accuracy values ranging from −9.2 to 10.4%, and a matrix effect ranging from −4 to 78%. The developed technique was used for the analysis of 27 vegetable oils.